Health self-management experiences of colorectal cancer patients in postoperative recovery: A qualitative study. (April 2021) - Lo, Pei-Shan; Lin, Yu-Ping; Hsu, His-Hsien; Chang, Shih-Chang; Yang, Shu-Ping; Huang, Wen-Chien; Wang, Tsae-Jyy
Abstract: Purpose: Health self-management helps improve health-related quality of life and life satisfaction, as well as cancer survival. The study aim was to explore the essence of the health self-management experiences and support needs of colorectal cancer patients after surgeries. Methods: The study was based on phenomenology research methodology. Purposive sampling was used to obtain a heterogeneous sample to provide rich information regarding the research questions. Participants were recruited from colorectal surgery outpatient clinics in a hospital in Taiwan. Data were collected by semi-structured in-depth interviews and analyzed by thematic content analysis. Strategies adapted from Lincoln and Guba were used to enhance the trustworthiness of the study. Results: Ten participants, 5 males and 5 females, were interviewed. Their health self-management experience fell into 3 overarching themes and 9 related subthemes. Our results show that (1) seeking support when experiencing discomfort, (2) when life changes, re-adjust accordingly, and (3) staying positive and self-perseverance are the essences of the health self-management experiences and support needs of postoperative colorectal cancer patients. Conclusions: Postoperative colorectal cancer patients experienced tremendous physical and psychosocial challenges after returning home from the hospital. Although burdened with multiple stressors, these patients were able to seek support, learning to practice self-care, facing cancer positively, and exhibit positive growth in life. Patients with colorectal cancer have to constantly adjust to the impacts of their diseases. The study results may provide as a reference for supporting postoperative adjustment and promoting health self-management among patients with colorectal cancer. Highlights: Transition to home after surgery requires a shift in self-management strategies. Patients try to control symptoms by following treatment plans and forming self-care. Patients desire info on dietary choices, follow-up, and keeping physical strength. Social support helps patients stay positive and be confident in overcoming cancer. Patients seek support, learn to self-care, and experience positive growth in life.